2014
DOI: 10.1016/j.protcy.2014.10.116
|View full text |Cite
|
Sign up to set email alerts
|

A Highly Recoverable and Efficient Filesystem

Abstract: Data recovery is a significant problem that presents a real challenge to forensics investigators today. File carvers have traditionally helped mitigate these difficulties. However, two issues still present significant challenges -1) Prior knowledge of file types is required for building file carvers, and 2) fragmentation prevents file carvers from successful recovery. In previous research, we proposed a framework for recovering deleted files without prior knowledge of file types and with the existence of fragm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…We tested it for Gandcrab and it was not able to identify it. [19] AFS [15] Hanson [20] Breeuwsma et al [21] Alhussein et al [22] Stoica et al [13] Huang et al [23] Alhussein et al [24] Baek et al [25] Lee et al [26] Continella et al [14] APEX [this work] Table I A COMPARISON OF RELATED WORKS WITH OURS Another technique by Huang et al [23] has been proposed for recovering encrypted data from flash drives. They provide a ransomware tolerant SSD which has firmware-level recovery systems, but the main drawback of their approach is that they keep multiple copies of data and hence need significantly more space than required.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…We tested it for Gandcrab and it was not able to identify it. [19] AFS [15] Hanson [20] Breeuwsma et al [21] Alhussein et al [22] Stoica et al [13] Huang et al [23] Alhussein et al [24] Baek et al [25] Lee et al [26] Continella et al [14] APEX [this work] Table I A COMPARISON OF RELATED WORKS WITH OURS Another technique by Huang et al [23] has been proposed for recovering encrypted data from flash drives. They provide a ransomware tolerant SSD which has firmware-level recovery systems, but the main drawback of their approach is that they keep multiple copies of data and hence need significantly more space than required.…”
Section: Related Workmentioning
confidence: 99%
“…Techniques that involve tagging of file blocks with some identifiers have been used by Alhussein et al in [22] and [24], where frameworks like FUSE have been used for development of forensic based file-systems. They provide forensic file identifiers at cluster-level file allocation to provide information needed for file types to be recovered after deletion.…”
Section: Related Workmentioning
confidence: 99%
“…Data recovery algorithms play an effective role during digital investigative procedures so the data on computer hardware has become one of the most important criminal evidence sought by investigators, in the United States alone, the FBI reported over 300,000 complaints of online criminal activity in 2011 [1][2][3][4][5], costing nearly $500,000,000. Data recovery depends primarily on the file system used to store and format data in different volumes (new technology file system (NTFS), file allocation table (FAT), extension (EXT), ANDROID) [6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%